Leprosy: clinical features and treatment - Lockwood, Diana N.J. (Henry Stewart Talks, 2022)
Leprosy disease Ridley-Jopling spectrum, Clinical signs of leprosy and leprosy presentation, Diagnostic tests for leprosy, Leprosy antibacterial treatment, Type 1 reactions, Erythema nodosum leprosum, steroid treatment, Neuropathic pain